2005
DOI: 10.1016/s1808-8694(15)31239-8
|View full text |Cite
|
Sign up to set email alerts
|

Endonasal dacryocystorhinostomy in children

Abstract: Our results confirm endoscopic endonasal dacryocystorhinostomy as an acceptable and safe method for treating children with nasolacrimal duct obstructions that are resistant to probings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Knijnik 5 reported complete relief of symptoms in 77.8% patients, Leibovitch et al 9 in 92.3% of patients, and Komínek and Cervenka 6 in 88.7%. Success rates in other studies were 100% as reported by Berlucchi et al, 4 94.4% by Gupta and Bansal, 7 and 91% by Eloy et al 1 In terms of external dacryocystorhinostomy, Maheshwari 17 reported a success rate of 97.5%, and Barnes et al 18 a success rate of 96%.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Knijnik 5 reported complete relief of symptoms in 77.8% patients, Leibovitch et al 9 in 92.3% of patients, and Komínek and Cervenka 6 in 88.7%. Success rates in other studies were 100% as reported by Berlucchi et al, 4 94.4% by Gupta and Bansal, 7 and 91% by Eloy et al 1 In terms of external dacryocystorhinostomy, Maheshwari 17 reported a success rate of 97.5%, and Barnes et al 18 a success rate of 96%.…”
Section: Discussionmentioning
confidence: 93%
“…14 While many studies of endoscopic dacryocystorhinostomy in adults are available in the literature, only a few reports of endonasal dacryocystorhinostomy in children have been published, with reported success rates of 82 to 88%. 1,[3][4][5][6][7][8][9][10] Intraoperatively, pediatric dacryocystorhinostomy can be bloodier than the procedure in adults, particularly at the beginning of the procedure when the nasal mucosa is resected. Also, suction is less effective in children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kominek et al (3) reported a 92.2% success rate. In another study, Knijnik (4) reported that 77.8% of primary endonasal endoscopic dacryocystorhinostomy procedures were successful. A total of 94.4% fulfilled the success criteria in another study (5) .…”
Section: Discussionmentioning
confidence: 99%
“…The first modern external DCR operation was realised by Toti in 1904 (2). In parallel with the medical-technological developments of the last decade, an extraordinary increase is being observed in the EDCR practices (4,5). In this study, we have evaluated the success rates of the cases on which bicanalicular silicon application was performed and those on which bicanalicular slicon application was not performed as well as the success rates of the cases to which T-tube was inserted to the lacrimal sac in company with the literature.…”
Section: Introductionmentioning
confidence: 99%